Examining the Role of ICT in Addressing Potential Issues in Indonesian Absentee Voting in Malaysia - Fridayani, Helen Dian; Chiang, Li Chun; Azzahra, Fadia (Universitas Muhammadiyah Ponorogo, 2024)
This paper investigates the challenges and potential solutions for absentee voting among Indonesian migrant workers in Malaysia during the 2024 General Election. Key issues include administrative inefficiencies, outdated voter lists, legal ambiguities, and vulnerabilities in postal voting, exacerbated by geographic and socio-economic barriers, particularly for rural and undocumented workers. Using qualitative content analysis with NVivo, the study explores how Information and Communication Technology (ICT), such as digital voter registration and blockchain voting, can enhance transparency, data accuracy, and election security. The research is novel in its focus on ICT solutions tailored to the unique challenges faced by Indonesian migrants in Malaysia, a topic that has been largely overlooked. It underscores the importance of coordinated efforts among government agencies, NGOs, and technology providers for effective implementation. While ICT offers promising opportunities for reform, challenges related to infrastructure, digital literacy, and voter trust remain significant. The study provides practical recommendations for improving absentee voting, with broader implications for countries with large expatriate populations, emphasizing the need for multi-stakeholder collaboration to ensure inclusivity and electoral integrity. Future recommendations should focus on addressing these challenges and maximizing the potential of ICT. Comprehensive policy reforms are needed to clarify legal ambiguities and streamline administrative processes, making voter registration and voting mechanisms more accessible and efficient. Governments should invest in robust digital infrastructure and implement digital literacy programs to empower migrant workers, especially those in rural areas or with undocumented status. Advanced technologies like blockchain should be further explored to enhance transparency, security, and data accuracy in absentee voting systems. Collaboration among government agencies, NGOs, and technology providers is essential for successful implementation. Future research should also examine the long-term impact of ICT-based voting systems on voter trust and participation, as well as conduct comparative studies with other countries facing similar challenges.